The prices of perishable food commodities in India: the impact of the lockdown - Ranjit Kumar Paul; Pratap S Birthal (Agricultural Economics Research Review, 2023)
Onions, potatoes, and tomatoes constitute an important component of the Indian diet. The COVID-19 pandemic in 2020 forced the government to impose a lockdown from 25 March to 31 May. This paper uses granular data to assess the impact of the lockdown on the daily arrivals and wholesale prices of these commodities at three metropolitan markets. The impact was significant and negative on the quantity traded, and positive on prices, but the heterogeneity across commodities and markets was considerable.